2021
DOI: 10.3389/fnagi.2021.698601
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Mechanism of Mitochondrial Autophagy in Cerebral Stroke

Abstract: Mitochondrial autophagy is an early defense and protection process that selectively clears dysfunctional or excessive mitochondria through a distinctive mechanism to maintain intracellular homeostasis. Mitochondrial dysfunction during cerebral stroke involves metabolic disbalance, oxidative stress, apoptosis, endoplasmic reticulum stress, and abnormal mitochondrial autophagy. This article reviews the research progress on the mechanism of mitochondrial autophagy in ischemic stroke to provide a theoretical basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…In the field of ischemic stroke and autophagy, through the econometric analysis of the literature published in the past decade, we found that both BNIP3 and LC3 are research hot spots and their interactions play a key role in nonselective autophagy after ischemic stroke. Mitochondrial BNIP3 binds to autophagosome LC3 to regulate cell death in ischemic stroke [36][37][38]. Mitochondrial dysfunction during ischemic stroke affects the level of autophagy, involving metabolic imbalance, oxidative stress, apoptosis, endoplasmic reticulum stress, and many other aspects, which may provide inspiration for the development of new targeted therapies for ischemic stroke [39][40][41][42][43][44][45].…”
Section: Related Workmentioning
confidence: 99%
“…In the field of ischemic stroke and autophagy, through the econometric analysis of the literature published in the past decade, we found that both BNIP3 and LC3 are research hot spots and their interactions play a key role in nonselective autophagy after ischemic stroke. Mitochondrial BNIP3 binds to autophagosome LC3 to regulate cell death in ischemic stroke [36][37][38]. Mitochondrial dysfunction during ischemic stroke affects the level of autophagy, involving metabolic imbalance, oxidative stress, apoptosis, endoplasmic reticulum stress, and many other aspects, which may provide inspiration for the development of new targeted therapies for ischemic stroke [39][40][41][42][43][44][45].…”
Section: Related Workmentioning
confidence: 99%
“…The oxidation method increases eggshell membrane solubility primarily by oxidizing the disulfide bonds between the fibers to sulfonic acid groups, thereby exposing more soluble fibrin to the solvent ( 53 ). The more effective oxidizing agent currently available is sodium dodecyl sulfate (SDS).…”
Section: Advances In Eggshell Membrane Proteolysis Technologymentioning
confidence: 99%
“…Mitochondrial dysfunction, including the overproduction of ROS, uncontrolled mitochondrial autophagy, and abnormal fission and fusion have been implicated in ischemic stroke ( Yang et al, 2018 ; Lei et al, 2021 ; Shi et al, 2022b ) . In addition, apoptosis, ATP disruption, calcium buildup, and faulty mitochondrial biogenesis contribute to aberrant ROS production during ischemic stroke ( Bai et al, 2021 ).…”
Section: The Nlrp3 Inflammasome and Its Function In Ischemic Strokementioning
confidence: 99%